Demonstrating Occupational Therapy's Distinct Value: Addressing the Quadruple Aim of Health Care Through Doctoral Capstone Projects - Ingrid Provident; Jennifer Lape (Scholarworks @ WMU, 2020)
The quadruple aim of health care focuses on enhancing health care systems through improving quality patient care, improving the health of populations, providing care in cost-efficient ways, and improving the experience of providing health care by decreasing provider and caregiver stress and burnout. The purpose of this retrospective review is to share how the curricular design and doctoral capstone process from one postprofessional occupational therapy doctorate program have been designed to support students in recognizing occupational therapy's distinct value in creating sustainable practice changes to move their respective health care systems forward. The postprofessional occupational therapy doctorate curriculum over 12 years has supported over 250 students in creating sustainable practice change projects in various work settings across the US. Doctoral capstone projects can be an effective platform for illustrating occupational therapy's distinct value by showing how occupational therapy services are unique and valuable in health care institutions. A strong curricular design with supports related to focusing on all aspects of the quadruple aim is an effective mechanism for enhancing care.